KEBIJAKAN POLITIK ANGGARAN PENDAPATAN DAN BELANJA DAERAH KABUPATEN SIGI - Mardiono, Eko; Darwis, Darwis; Mansur, Sastrio (Katalogis, 2018)
This research uses theory of Thompson and McEwen (2006), Bargaining (bargaining), Kooptasi (cooptation), and the Coalition (the coalition), it can be concluded that the bargaining factor development programs as a result of "reses" and "musrenbang" for political policy formulated budget year 2017 lasted "less good" that give impact on the lack of consistency of development programs that have been the aspiration of the community.Bargaining program development is alternative in result because of lack of funding a GRANT solution at the time. Then the factor cooptation and coalition are not integral part of the political policy formulation of the local budget (APBD) in 2017. Local Legislative (DPRD) and local government Sigi County each have run task and function based on the Act. It's just that accommodate various suggestion and aspiration into depth because of limited fund, the impact was less public confidence toward local government and local legislative Sigi County. This resulted in a lack of public trust in the Sigi regency in any budget formulation policy.